Primary female epispadias: Perineal approach or Kelly repair?. Issue 1 (February 2018) - Leclair, Marc-David; Faraj, Sébastien; Villemagne, Thierry; Carrouget, Julie; Arnaud, Alexis; Heloury, Yves
Summary: Objectives: Primary female epispadias encompasses a spectrum of disease, presenting with a variable degree of incontinence. We hypothesized that although perineal urethrocervicoplasty can be a successful first-line procedure in patients with normal bladder, a more radical reconstruction was necessary to achieve continence in cases lying at the most severe end of the spectrum. Our aim was to assess the results of a surgical management using perineal approach in girls with normal bladder capacity, and Kelly radical soft-tissue mobilization (RSTM) in patients with inadequate bladder, based on the assumption that bladder capacity (BC) is a reliable marker of epispadias severity. Study design: Prospective inclusion of incontinent girls with female epispadias referred to a single institution. Patients with normal BC were treated with perineal urethrocervicoplasty (PUCP, group 1). Patients with small bladder underwent RSTM (group 2). Follow-up was at 1, 3, 6, and 12 months postoperatively, then annually, including physical examination, renal ultrasound at each visit, continence status, and estimation of functional/maximal BC. The main study outcome was continence status at the age of 5 years or later, if postoperative follow-up was >12 months. Results: From 2006 to 2017, 16 consecutive children were prospectively included in this study, at a median age of 39 months (5–102 months). Seven girls were included in group 1 and underwent PUCP; at the last follow-up, five out of seven were dry by day (4/5 day and night), although three out of five required bladder-neck injection after perineal reconstruction due to stress incontinence. Two patients with persistent incontinence and absence of BC increase after PUCP subsequently underwent RSTM. Eleven patients with low BC (56% [10–94%] of expected BC) were included in group 2 (9 without prior surgery, 2 after PUCP failure). Among the eight evaluable patients, eight out of eight achieved diurnal continence, and 3/8 were fully continent. One girl with obstructive micturition required clean intermittent catheterization. Discussion: The traditional approach of female epispadias based on staged reconstruction (urethroplasty followed by bladder-neck reconstruction) raised concerns regarding the risk of non-physiological obstructive micturition. The perineal approach was suggested as an alternative, with reported diurnal continence rates of 60–80%, but less than 50% of nocturnal continence, presumably in relation with limited bladder capacity. In cases selected within the most severe end of the epispadias spectrum, the Kelly RSTM seems to offer excellent continence rates. Conclusion: A tailored approach to female epispadias, based on perineal reconstruction in favorable cases, and radical soft-tissue mobilization in severe cases, seems to yield good continence outcomes in the long term.